The Relationship Between Nurses’s Caring Behavior and Self-Efficacy in HIV/AIDS Patients - Viere Allanled Siauta; Angela Librianty Thome (GLOBAL HEALTH SCIENCE GROUP, 2026)
The number of HIV/AIDS patients in Jayapura City continues to increase every year. The role of nurses is essential in caring for HIV/AIDS patients. One strategy that can be implemented is caring behavior. Caring behavior has significant benefits in nursing and can improve the quality of nursing care. Objective: This study aims to determine the relationship between nurses' caring behavior and self-efficacy in HIV/AIDS patients. Method: This study is a quantitative study with an analytical design and a cross-sectional approach. The sample size in this study was 35 respondents using the Lemeshow formula for estimating the unknown population proportion. Data were collected from respondents through interviews and questionnaire. Data analysis was conducted in two stages : univariate analysis to describe the characteristics of respondents, caring behavior and self-efficacy,and bivariate anlysis using Chi-Square to assess the relationship between nurses’s caring behavior and self-efficacy. Results: The results showed that the majority of nurses' caring behavior was moderate (57.1%). Most respondents had good self-efficacy (40.0%). The chi-square test results obtained a p-value of 0.003, so it can be concluded that there is a relationship between nurses' caring behavior and self-efficacy in HIV/AIDS patients at the Hana Clinic, Yowari Regional Hospital, Jayapura Regency. Conclusions: The results of this study indicate that nurses' caring behavior plays an important role in increasing self-efficacy in HIV/AIDS patients.